LIVING WITH THE LABELING DISEASE FOR 25 YEARS - Gallian, Joseph A. (Journal of the Indonesian Mathematical Society, 2011)
In this article I trace my involvement with graph labeling for the past 25 years. I provide some statistical information about the growth in interest in graph labeling and some open problems that I believe are accessible.DOI :Â http://dx.doi.org/10.22342/jims.0.0.18.45-58